Presymmetry in the Standard Model with Adulterated Dirac Neutrinos - Matute-Carvajal, E (World Scientific, 2015)
Recently we proposed a model for light Dirac neutrinos in which two right-handed (RH) neutrinos per generation are added to the particles of the Standard Model (SM), implemented with the symmetry of fermionic contents. The ordinary one is decoupled via the high scale type-I seesaw mechanism, while the extra pairs off with its left-handed (LH) partner. The symmetry of lepton and quark contents was merely used as a guideline to the choice of parameters because it is not a proper symmetry. Here we argue that the underlying symmetry to take for this correspondence is presymmetry, the hidden electroweak symmetry of the SM extended with RH neutrinos defined by transformations which exchange lepton and quark bare states with the same electroweak charges and no Majorana mass terms in the underlying Lagrangian. It gives a topological character to fractional charges, relates the number of families to the number of quark colors, and now guarantees the great disparity between the couplings of the two RH neutrinos. Thus, Dirac neutrinos with extremely small masses appear as natural predictions of presymmetry, satisfying the t Hooft s naturalness conditions in the extended seesaw where the extra RH neutrinos serve to adulterate the mass properties in the low scale effective theory, which retains without extensions the gauge and Higgs sectors of the SM. However, the high energy threshold for the seesaw implies new physics to stabilize the quantum corrections to the Higgs boson mass in agreement with the naturalness requirement. © 2015 World Scientific Publishing Company.